Modelling and PID value search for antilock braking system (ABS) of a passenger vehicle - Abdul Majid, M. M. (Society of Automotive Engineers Malaysia, 2017)
This paper presents the methodologies use in determining the PID value of an Antilock Brake System (ABS) of a Malaysian made passenger vehicle. The research work involves experimental work for data acquisitions, development of braking model, parameter tuning for both simulation model parameter and PID values search. A Malaysian made car is equipped with instrumentation used to collect vehicle behaviour during normal and hard braking manoeuvres. The data collected are the vehicle's stopping distance and longitudinal speed. The data during the normal braking are used to validate a two degree of freedom (2 DOF) of vehicle's braking model, while the data collected during the hard braking are used to search for the PID value used to control the operation of the ABS system. The developed simulation model of a braking system correlates well with the experimental data and the tuning done on the PID algorithm indicates that the ABS is controlled by the PI system.